2021
DOI: 10.1007/s12144-021-01619-5
|View full text |Cite
|
Sign up to set email alerts
|

The adult sex ratio of European regions predicts female, but not male, subjective well-being

Abstract: In recent years, researc in subjective well-being has found several ecological factors that may underpin societal differences in happiness. The adult sex ratio, the number of males relative to females in an environment, influences many behaviours in both humans and non-human animals. However, the possible influence of the sex ratio on subjective well-being has received little attention. I investigated the relationship between the adult sex ratio and subjective well-being in over 29,000 respondents from 133 reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
2
3
0
Order By: Relevance
“…Previous studies showed that gender was an important factor in subjective well-being, especially after middle age, when the subjective well-being gap between the sexes became more pronounced ( Meisenberg and Woodley, 2015 ; Senik, 2017 ). In this study, middle-aged and older men had higher subjective well-being than women, consistent with previous findings ( Richardson, 2021 ). A study that included 95 countries showed that subjective well-being was higher for women in 50 countries and for men in 45 countries, with women having higher subjective well-being than men on average, which correlated with the level of gender equality in the country ( Arrosa and Gandelman, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies showed that gender was an important factor in subjective well-being, especially after middle age, when the subjective well-being gap between the sexes became more pronounced ( Meisenberg and Woodley, 2015 ; Senik, 2017 ). In this study, middle-aged and older men had higher subjective well-being than women, consistent with previous findings ( Richardson, 2021 ). A study that included 95 countries showed that subjective well-being was higher for women in 50 countries and for men in 45 countries, with women having higher subjective well-being than men on average, which correlated with the level of gender equality in the country ( Arrosa and Gandelman, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Social need fulfillment exceeded an individual’s fulfillment of their own needs in predicting subjective well-being ( Tay and Diener, 2011 ). Therefore, considering the global gender inequality ( United Nations Development Programme, 2016 ), women have lower subjective well-being than men on average ( Richardson, 2021 ). However, it was also shown that there was no significant difference in subjective well-being between older men and women ( Liu, 2011 ).…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…These effects for actual sex ratio were not found with males. The finding that the actual sex ratio was linked to female life satisfaction but not male life satisfaction is consistent with what was reported in a recently published analysis by Richardson (2023). Using the responses from two large sample European surveys, he found that female subjective well-being was higher in European regions that had a higher percentage of males.…”
Section: Discussionsupporting
confidence: 87%
“…On American campuses, female preponderance correlates with more hookups and sex partners, and an attitude toward copulation as something that does not require love ( Adkins et al, 2015 ). Women’s subjective well-being is reduced ( Richardson, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…They are more inclined to marry and do so earlier in life ( South and Trent, 1988 ). Women’s well-being increases without being offset by a reduction in overall male well-being, as an increase in marriage also benefits men ( Richardson, 2021 ). Men are less violent, choosing instead to compete with other men economically ( Guttentag and Secord, 1983 ; Pedersen, 1991 ; Barber, 2000 , 2009 ; Maner and Ackerman, 2020 )—although in some contexts, violence can increase ( Filser et al, 2021 ; South et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%